Heat and mass transfer in combustion of coal dust into the combustion chamber of the power boiler BKZ-75 of Shahtinskaya TPP - Maximov, V.Ju.; Aidabol, S.K.; Otynshyeva, N.A. (Recent Contributions to Physics, 2018)
The presented work is devoted to the processes of heat and mass transfer, which occur when burning of pulverized coal in the combustion chamber of the existing energetic boiler BKZ-75 of the Shakhtynskaya TPP and applied to such processes methods of 3D-computer simulation. Research which was conducted in this paper, allow determining the basic patterns of distribution of aerodynamic and heat-exchanging characteristics in all volume of the combustion chamber of the boiler BKZ-75 of Shakhtynskaya TPP and on an output from it. In this paper has been compared of configurations by burner devices of the combustion chamber in the following cases: 1) are used direct-flow slot-hole torches (the basic mode); 2) vortex burner with a swirling of aero mix and their inclination to the center a symmetry of a boiler by 30 degrees. In addition, conducted in this paper the researches allowed determining the influence of emergency stopping of supply of a coal dust in burners on the main characteristics of the combustion chamber.
Keywords: numerical simulation, combustion chambers, pulverized coal, thermal characteristics, temperature, aerodynamics, heat transfer